Flow of mangrove ecosystem services to coastal communities in the Brazilian Amazon - Owuor, Margaret; Santos, Thuareag M. T.; Otieno, Philip; Mazzuco, Ana Carolina A.; Iheaturu, Chima; Bernardino, Angelo F. (Frontiers in Environmental Science, 2024)
Mangrove forests are broadly recognized to support a variety of ecosystem services on coastal margins worldwide. These services may significantly contribute to the well-being of millions of people, but there is limited information about their importance in the Global South. This study mapped for the first time the flow of ecosystem services in Brazilian Amazon mangroves, which represent over 700,000 ha of mangroves in the country. We also identified the spatial changes in the flow of services across coastal landscapes, including urban, agricultural upland areas and coastal natural protected areas. Our matrix model indicated that mangroves, waterbodies, sandflats and mudflats are critical to the flow of multiple ecosystem services, including provisioning (fish, mariculture), cultural (historical and intrinsic value, research, and education), and regulation (climate, flood control, nursery, and breeding grounds). Social economic context, occupation, education, and residence time are important factors influencing villagers to identify the flow of ecosystem services, which could be compared across other coastal marine reserves in South America that have similar management of natural resources. Adjacent coastal upland habitats such as forests and croplands are important to support many provisioning ecosystem services to coastal villagers that would otherwise be obtained from mangroves, suggesting that protecting these connected habitats and supporting small-scale agriculture may help to avoid deforestation of mangrove forests. As over 80% of the mangroves in the country are managed as extractive reserves and may support communities with comparable socio-economic characteristics, we provide a foundation for the development and replication of ecosystem services assessments in Brazilian mangroves, which cover an area of